LEVERAGING TECHNOLOGY TO ENHANCE THE PROFESSIONAL SKILLS OF EDUCATORS - Tleumbetova Kalligul Dlimbetovna; Reyimbergenova Dilnoza Farkhadovna (Journals Park Publishing, 2023)
In the rapidly evolving landscape of education, educators are faced with the challenge of staying abreast of technological advancements that can transform their teaching methods and enhance the learning experience for students. Embracing technology is not just a trend; it has become a necessity for educators to remain effective in their roles. In this article, we will explore various ways in which technology can be employed to improve the professional skills of educators.
Keywords: Online learning, Virtual reality, Augmented reality, Collaborative learning, Artificial intelligence, Gamification, E-learning platforms, Webinars, Digital assessment, Podcasts, Cybersecurity, Digital literacy, Mentorship programs.